2010
DOI: 10.1007/s11136-009-9581-0
|View full text |Cite
|
Sign up to set email alerts
|

Factorial structure and validity of the Multicultural Quality of Life Index

Abstract: The MQLI has high internal consistency, can be interpreted in terms of a single factor, and has an adequate convergent validity, although its absolute correlations with depression and with the WHOQOL-BREF were equally high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
(27 reference statements)
2
8
0
1
Order By: Relevance
“…We believe the current study contributes to cultural relevance by the fact that the authors have intentionally paid close attention to the cultural and linguistic precision of each item. In terms of time efficiency, and consistent with the literature [10,[16][17][18][19][20], participants in the pilot test reported MQLI-Gr was easy to understand and took only a few minutes to complete. Congruent with earlier validation studies of MQLI [16][17][18][19][20], this study demonstrated good internal consistency.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We believe the current study contributes to cultural relevance by the fact that the authors have intentionally paid close attention to the cultural and linguistic precision of each item. In terms of time efficiency, and consistent with the literature [10,[16][17][18][19][20], participants in the pilot test reported MQLI-Gr was easy to understand and took only a few minutes to complete. Congruent with earlier validation studies of MQLI [16][17][18][19][20], this study demonstrated good internal consistency.…”
Section: Discussionsupporting
confidence: 75%
“…To assess internal reliability, internal structure, and construct validity, the following analyses were conducted: Cronbach's α coefficient, confirmatory factor analysis (CFA), independent t-test, and ANOVA. A confirmatory factor analysis (CFA) [28] was conducted to evaluate a one-factor model (personal satisfaction) [18]. The following four indexes along with cut-off criteria [29]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous article showed a correlation between the MQLI and the World Health Organization Quality of Life Assessment-Bref (WHOQOL-BREF) in women at the postpartum period [24]. The MQLI has been validated in Peru [25], Argentina [26], Spain [27], Brazil [28], China [29] and Korea [30].…”
Section: Introductionmentioning
confidence: 99%